Principal's Policy in Islamic Religious Education in the Digital Era at Makhad Al Khadijah MAN 1 Jember - Ahmad Ikhsan Dimyati (Yayasan Dinamika Ilmu Banyuwangi, 2025)
The digital era brings significant changes in various aspects of life, including in the world of education. School principals as educational leaders have a strategic role in designing policies to improve the effectiveness of learning, especially in Islamic Religious Education (PAI) subjects. This study aims to analyze the principal's policy in Islamic religious education in Ma'had Al Khadijah MAN 1 Jember and identify the challenges and opportunities that arise in the digital era. This research used a qualitative approach with a case study method. Data were obtained through in-depth interviews, observation, and documentation which were then analyzed using descriptive-analytical techniques. The results showed that the principal's policy in Ma'had Al Khadijah MAN 1 Jember in Islamic religious education focuses on three main aspects: (1) Integration of technology in Islamic religious education learning through the use of digital platforms and Islamic-based applications; (2) Strengthening students' religious character through digital-based programs that maintain traditional pesantren values; and (3) Increasing teachers' competence in utilizing technology to present more interactive and interesting teaching materials for students. However, in implementing the policy, there are various challenges, such as limited digital infrastructure, the readiness of educators, and the potential degradation of Islamic values due to uncontrolled exposure to technology. Therefore, synergy between school principals, teachers, students, and parents is needed so that the implemented policy can run effectively and in accordance with the objectives of Islamic education.